2013
DOI: 10.1161/strokeaha.111.000605
|View full text |Cite
|
Sign up to set email alerts
|

Low Plasma Arginine:Asymmetric Dimethyl Arginine Ratios Predict Mortality After Intracranial Aneurysm Rupture

Abstract: Background-Asymmetrical dimethylarginine (ADMA), an endogenous inhibitor of nitric oxide synthases, predicts mortality in cardiovascular disease and has been linked to cerebral vasospasm after aneurysmal subarachnoid hemorrhage (SAH). In this prospective study, we assessed whether circulating ADMA, arginine:ADMA ratio, and nitrite/nitrate levels were associated with survival and cerebral vasospasm in SAH patients. Methods-One hundred and eleven patients were observed day 1 to 15 after SAH, with serial measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 51 publications
2
18
1
Order By: Relevance
“…A study by Staalso et al, found that low arginine:ADMA ratio in the first week after SAH is predictive of mortality during the first thirty days (37). Interestingly, high ADMA levels are associated to increased mortality in cardiac pathologies, such as coronary artery disease, chronic heart failure, and peripheral artery disease.…”
Section: Hormones/enzymesmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Staalso et al, found that low arginine:ADMA ratio in the first week after SAH is predictive of mortality during the first thirty days (37). Interestingly, high ADMA levels are associated to increased mortality in cardiac pathologies, such as coronary artery disease, chronic heart failure, and peripheral artery disease.…”
Section: Hormones/enzymesmentioning
confidence: 99%
“…Finally, another investigation, carried on in 111 patients, reported that a low arginine/ADMA (asymmetric dimethylarginine) ratio in the first week after SAH is predictive of mortality during the first 30 days and that inversely correlates with nitrite/nitrate levels (37).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest the article by Staalsø et al 1 pertaining to the relationship between asymmetrical dimethylarginine (ADMA), an endogenous inhibitor of nitric oxide (NO) synthase, and survival in patients with aneurysmal subarachnoid hemorrhage. The results of their study demonstrated that a low arginine:ADMA ratio in the first week after subarachnoid hemorrhage predicted mortality rate in the first 30 days.…”
Section: To the Editormentioning
confidence: 99%